Raising of Microvascular Flaps A Systematic Approach - Wolff, Klaus-Dietrich (Springer International Publishing, 2018)
This book provides all who are involved in microsurgical tissue transfer, including plastic surgeons, ENT surgeons, trauma surgeons, and oral and maxillofacial surgeons, with all the knowledge they will need in daily practice. The new third edition continues with the didactic principle of splitting up complex surgical procedures into a series of simple steps, guided by clearly defined donor site-specific landmarks. For each flap, an anatomically based system of step-by-step procedures is proposed that best combines simplicity, safety, and reliability for successful flap harvesting. Photographs of each step are accompanied by schematic color drawings to enhance understanding of the anatomy. Surgical techniques are also shown in every detail in supplementary videos available online. Additional features in this edition include highly useful modifications of elevation of the radial forearm flap as well as new chapters on the rectus abdominis flap, a reliable option for covering deep and extended defects, and the medial sural perforator flap. Like the previous editions, the book will serve as a quick source of focused and straightforward information valuable for any reconstructive surgeon.